Relationship of Pregnant Women's Knowledge of Dental And Oral Heath Maintenance With Gingivitis Status - Farah Fuadiyah; Silvia Prasetyowati; Agus Marjianto (International Journal of Advanced Health Science and Technology, 2024)
Pregnant women are a group that requires special attention to their oral heath. Pregnant women often neglect their oral hygiene which wil cause plaque buildup on the teeth and gingival margin, this can cause gingival inflammation or gingivitis. One of the efforts that can be done to prevent gingivitis is to reduce eating cariogenic foods and brushing teeth properly and regulaly and what can be done by heath workers by providing education to increase their knowledge about gingivitis. Problems: The status of gingivitis among pregnant women at BPS (Private Practice Midwife). Objective: To know the relationship between knowledge of oral heath maintenance of pregnant women and gingivitis status. Method: This type of research is analytic research with cross sectional method, with a sample of 56 pregnant women. The data analysis technique uses a normality test, namely Kolmogorov-Smirnov after the Chi-Square test. Result: There is no relationship between the knowledge of dental and oral heath maintenance of pregnant women with gingivitis status.